Testing pays off twice: Potentials of practice tests and feedback regarding exam performance and judgment accuracy - Naujoks, Nick; Harder, Bettina; Händel, Marion (Metacognition and Learning, 2022)
Two studies investigated the testing effects on performance and on metacognitive judgment accuracy in authentic learning settings. Across two educational psychology courses, undergraduate students had the opportunity to voluntarily participate in four different practice tests during the term—without feedback in Study 1 (N = 201 students) or with individual corrective feedback in Study 2 (N = 111 students). Across studies in real classroom settings with and without feedback, regression analyses indicated that a higher number of taken practice tests were related to higher performance in the final course exam and to two scores of metacognitive judgment accuracy (absolute accuracy and sensitivity). However, students’ preparation and post-processing practice tests, their perceived usefulness of tests for monitoring one’s performance, and metacognitive specificity differed depending on whether students received feedback or not. Overall, the studies convey considerable evidence on how participation in practice tests is related not only to performance but also to monitoring accuracy in authentic learning settings.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Feedback; Metacognitive judgments; Performance; Testing